Complicated legacies: The human genome at 20 - Kathryn Maxson Jones; Robert Cook‐Deegan; Charles N. Rotimi; Shawneequa Callier; Amy R. Bentley; Hallam Stevens; Kathryn A. Phillips; Jeroen P. Jansen; Christopher F. Weyant; Dorothy E. Roberts; Dina Zielinski; Yaniv Erlich; et al. (2021)
Millions of people today have access to their personal genomic information. Direct-to-consumer services and integration with other “big data” increasingly commoditize what was rightly celebrated as a singular achievement in February 2001 when the first draft human genomes were published. But such remarkable technical and scientific progress has not been without its share of missteps and growing pains. Science invited the experts below to help explore how we got here and where we should (or ought not) be going.